Voltammetric Determination of Iron(III) in Water - Lu, M; Compton, R (2013)
A square wave voltammetric procedure for the determination of trace amounts of Fe(III) was developed at an unmodified edge plane pyrolytic graphite (EPPG) electrode and a screen printed electrode (SPE). This simple procedure was applied to real samples of commercially bottled mineral water. Sensitive results in the micromolar region could be achieved without modification of the electrode. Using the WHO guideline limits for the Fe(III) concentration in drinking water, recovery percentages at an EPPG gave 103% and 107%, and 98.6% and 95.0% at a SPE for the 5.36μM (0.3mgL-1) and 53.6μM (3.0mgL-1) additions of Fe(III), respectively. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.